2018
DOI: 10.3892/ol.2018.8091
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin induces DNA damage response under hypoxic condition in myeloma cells

Abstract: Hypoxia serves a crucial role in the development of drug resistance in various cancer cells. Therefore, many attempts targeting hypoxia are underway to overcome the drug resistance mediated by hypoxia. This strategy is useful for multiple myeloma (MM) cells, as MM cells reside within the bone marrow, where oxygen concentrations are relatively low. A natural compound library was screened to identify compounds exerting cytotoxicity in MM cells under hypoxic conditions. Bufalin exhibited marked cytotoxicity to MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Bufalin, a component of traditional Chinese medicine, has been found to induce apoptosis in several types of cancers. 78 , 79 Interestingly, it has been found to suppress cervical cancer tumorigenesis and to enhance paclitaxel therapy by suppressing α2/FAK/AKT1/GSK3β signaling. 80 Furthermore, a component in snake venom called aggretin can bind to integrin α2β1.…”
Section: Role Of Integrin α2 In Diseasesmentioning
confidence: 99%
“…Bufalin, a component of traditional Chinese medicine, has been found to induce apoptosis in several types of cancers. 78 , 79 Interestingly, it has been found to suppress cervical cancer tumorigenesis and to enhance paclitaxel therapy by suppressing α2/FAK/AKT1/GSK3β signaling. 80 Furthermore, a component in snake venom called aggretin can bind to integrin α2β1.…”
Section: Role Of Integrin α2 In Diseasesmentioning
confidence: 99%
“…The natural product Chansu enriched with bufalin has long been used in practice as painkiller, detoxicant and cardioactivator as traditional medicine in East Asia. The antitumour activity of bufalin has been recently reported in multiple cancer types including prostate cancer, gastric cancer, colorectal cancer, lung cancer, breast cancer, endometrial cancer, hepatocellular carcinoma and leukaemia 13‐17 . The mechanism of bufalin is multifaceted 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The antitumour activity of bufalin has been recently reported in multiple cancer types including prostate cancer, gastric cancer, colorectal cancer, lung cancer, breast cancer, endometrial cancer, hepatocellular carcinoma and leukaemia. [13][14][15][16][17] The mechanism of bufalin is multifaceted. 25 Most of the study found its pro-apoptotic activity via regulation of Bcl-2/Bax and Bcl-X and activation of caspase-9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations